Polysialylation of the Neural Cell Adhesion Molecule: Setting the Stage for Plasticity Across Scales of Biological Organization - Amoureux, Marie-Claude; Viallat, Annelise; Giribone, Coralie; Benezech, Marion; Marino, Philippe; Millet, Gaelle; Boquet, Isabelle; Norreel, Jean-Chrétien; Rougon, Geneviève (IntechOpen, 2012)
None